Establishment of a prospective cohort of mechanically ventilated patients in five intensive care units in Lima, Peru: protocol and organisational characteristics of participating centres. - Denney, Joshua A. (2015)
Introduction: Mechanical ventilation is a cornerstone in the management of critically ill patients worldwide; however, less is known about the clinical management of mechanically ventilated patients in low and middle income countries where limitation of resources including equipment, staff and access to medical information may play an important role in defining patient-centred outcomes. We present the design of a prospective, longitudinal study of mechanically ventilated patients in Peru that aims to describe a large cohort of mechanically ventilated patients and identify practices that, if modified, could result in improved patient-centred outcomes and lower costs. Methods and analysis: Five Peruvian intensive care units (ICUs) and the Medical ICU at the Johns Hopkins Hospital were selected for this study. Eligible patients were those who underwent at least 24 h of invasive mechanical ventilation within the first 48 h of admission into the ICU. Information on ventilator settings, clinical management and treatment were collected daily for up to 28 days or until the patient was discharged from the unit. Vital status was assessed at 90 days post enrolment. A subset of participants who survived until hospital discharge were asked to participate in an ancillary study to assess vital status, and physical and mental health at 6, 12, 24 and 60 months after hospitalisation, Primary outcomes include 90-day mortality, time on mechanical ventilation, hospital and ICU lengths of stay, and prevalence of acute respiratory distress syndrome. In subsequent analyses, we aim to identify interventions and standardised care strategies that can be tailored to resource-limited settings and that result in improved patient-centred outcomes and lower costs.